Tinjauan Yuridis terhadap Penegakan Hukum Tindak Pidana Penyelundupan Bibit Lobster - I Made Agus Sanjaya; I Made Minggu Widyantara; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Smuggling is common given the fact that marine products are very attractive. In a really basic way, transactions of billions of rupiah can be carried out illegally, mostly by avoiding the customs office of different rates provided by Customs. Currently, the Government is trying to prevent the smuggling of marine products that are prohibited for trading, because in addition to harming the State, this can result in minimal marine biota and losses of up to trillions. The purpose of this study is to determine the regulation regarding the prohibition of catching lobster seeds and law enforcement against the crime of smuggling lobster seeds, the type of normative legal research. The sources of this research are obtained through approaches by examining based on statutory regulations, legal principles, and legal doctrines to respond to legal themes encountered in order to obtain new opinions, thoughts and understandings as rules for ending events that occur. The sources of this research are obtained through approaches by examining based on statutory regulations, legal principles, and legal doctrines to respond to legal themes encountered in order to obtain new opinions, thoughts and understandings as rules for ending events that occur. The guidelines for catching lobster seeds have recently been regulated in the Minister of Marine Affairs and Fisheries Regulation No. 56 / PERMEN-KP / 2016 concerning the Prohibition of Catching and or Exporting Lobster, Crab and Crab. In 2020 the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia again provided guidelines Number 12 / PERM EN -KP / 2020 concerning Management of Lobster and Crabs. Which indirectly opens the export of lobster seeds in Indonesia.